KEJAHATAN DAN CAMPUR TANGAN TUHAN - Mustofa, M. Lutfi (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2004)
Evil is the problematic thing if it is related to God and the source of evil. According to atheist, dualist and polytheist; evil is the empiric reality, its existence beside goodness cannot be refused. In the further explanation, mean that there is other power beside God power, which creates evils, because it is impossible for The Sacred God to create evils.Muslim philosophers, according to Muttahhari, denied that argument, because in their opinion, if there is other power beside God power, which creates evils, means syirk (dualist or polytheist); something to be avoided in religious ground (tauhid). Muttahhari argued it is true that evil is empiric reality but it is relative. The universe comes into being from The Ultimate Good and work with a good system. Then the evil occurs when the system works in disproportional way or one of the components work out of the rule. Furthermore, evil is temporal and disorderliness, it is not a system or an ethic.Keyword: evil, good, and God.